2015
DOI: 10.1104/pp.114.253229
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Primary Lesion of Toxic Aluminum in Plant Roots  

Abstract: Despite the rhizotoxicity of aluminum (Al) being identified over 100 years ago, there is still no consensus regarding the mechanisms whereby root elongation rate is initially reduced in the approximately 40% of arable soils worldwide that are acidic. We used high-resolution kinematic analyses, molecular biology, rheology, and advanced imaging techniques to examine soybean (Glycine max) roots exposed to Al. Using this multidisciplinary approach, we have conclusively shown that the primary lesion of Al is apopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(185 citation statements)
references
References 35 publications
11
155
2
10
Order By: Relevance
“…The initial effect of toxic Al is a deleterious effect on cell expansion resulting in a decrease in the elemental elongation rate, one possibility is through affecting the loosening of the cell walls (Kopittke et al, 2015). Here we observed that the Al-induced JA signaling increase in root tips occurred after 2-h Al exposure (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The initial effect of toxic Al is a deleterious effect on cell expansion resulting in a decrease in the elemental elongation rate, one possibility is through affecting the loosening of the cell walls (Kopittke et al, 2015). Here we observed that the Al-induced JA signaling increase in root tips occurred after 2-h Al exposure (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 56%
“…However, cell division is a slow process, while the inhibition of root elongation of Al-sensitive maize can occur within 30 min of Al treatment (Llugany et al, 1995). Recently, Kopittke et al (2015) reported that 75 mM Al reduced root growth of soybean after only 5 min, with Al being toxic by binding to the walls of outer cells, which directly inhibited their loosening in the elongation zone, and concluded that the primary lesion of Al is apoplastic. Therefore, the rapid dynamics of root growth to Al stress indicates that Al first inhibits root cell expansion and elongation and later on also cell division (Horst et al, 2010;Kochian et al, 2015).…”
mentioning
confidence: 99%
“…Aluminum is thought to bind to the cell wall preventing loosening as required for root elongation (Kopittke et al, 2015). Plant debilitation may also be affected by changes in pH due to the coal fly ash.…”
Section: Adverse Consequences Of Aerosolized Coal Fly Ashmentioning
confidence: 99%
“…For metals such as Na, it is known that plant growth is reduced due to osmotic effects, direct toxicity, and indirect nutritional effects (Munns and Termaat 1986;Parida and Das 2005). In contrast, for Al, root elongation is reduced rapidly due to the binding of Al to the cell wall which inhibits its loosening within the elongation zone as required for growth (Jones et al 2006;Kopittke et al 2015). Yet, despite these marked differences between Na and Al toxicity (for example), it is also known that there are also some commonalities in the toxic effects of various metals.…”
Section: Introductionmentioning
confidence: 99%